Microfluidic intestine-on-a-chip: Current progress and further perspectives of probiotic-foodborne pathogen interactions. (April 2023) - Xiang, Xinran; Wang, Xinbin; Shang, Yuting; Ding, Yu
Abstract: Background: Standard two/three dimensional (2D/3D)-cell culture platforms facilitate the understanding of communication between various cell types and their microenvironments. However, they are still limited in generalizing complex functions in vitro . Microfluidic intestine-on-a-chip models have been emerging as a novel platform to study intestinal function in health and disease, especially the interactions between probiotics and pathogens. Scope and approach: This review aims at the recent advances in intestine-on-a-chips for studying the interactions between probiotics and pathogens in the gut. The review elucidates the general design ideas of intestine-on-a-chips, including the chip materials, cell sources, stimulation, and the methods to quantify the integrity of the intestinal barrier. Moreover, this study provides a summary of the latest progress in the application of intestine-on-a-chip to probiotic-pathogen interactions, meanwhile discusses the current challenges and future development direction of intestine-on-a-chips. Key findings and conclusions: Intestinal microecology is an extremely complex system. Intestine-on-a-chips provide powerful platforms in vitro for studying probiotic-pathogen interactions and helping to promote the development of probiotics in the prevention and treatment of intestinal diseases. Future studies should break the limitations of traditional models, so as to make it closer to the internal environment and more suitable for cost-effective large-scale analysis of food-intestine-disease interactions. Highlights: Advances in intestine-on-a-chips for studying probiotic-pathogen interactions are summarized. General design ideas of intestine-on-a-chip were elucidated. Methods to quantify the integrity of the intestinal barrier were summarized. Prospective trends for future intestine-on-a-chips are proposed.